EXAMINING WOMANHOOD: NARRATIVES OF WOMEN’S SUBJUGATION AND NON-SURVIVAL IN FIVE SHORT STORIES FROM ASIA - Shara Rose Virgini Olaya Dionaldo; Andrea Gomez Soluta (International Journal of Humanity Studies (IJHS), 2021)
This paper explores the discourse on womanhood in the Asian context by delving into the narratives of women characters in five short stories by three Asian writers. Specifically, it attempted to determine the images associated with Asian women based on the portrayal of the main protagonists in the selected short stories. It then analysed how these images construct womanhood and perpetuate such ideal in the Asian mindset. Viewed from both formalist and constructionist lenses, findings show that the women protagonists are relegated to their three-pronged traditional roles/images: daughter, wife, and mother. These images, in turn, shape how these characters behave and are seen by other characters - submissive, self-sacrificing and subjugated. However, despite an unrelentingly difficult life, all the five women still struggle to survive. Such act seems inconsistent with the above stereotypical construct of womanhood, though a closer look actually shows a different side to the said construct: strong, steadfast and resilient/survivalist. Not all of the protagonists overcome their tragic lives. Nonetheless, all five women manage to convey that the concept of womanhood is more complex than how it had been perceived in the past. This complexity is clearly illustrated in the lived realities of many Asian women today.